Fazlur Rahman’s Neo-Modernist Thought and the Epistemological Critique of Knowledge Integration in Indonesian Islamic Education - Amelina, Naila; Munir, Munir; Ismail, Ismail; Razzaq, Abdur; Jhoni, Muhammad (LPPM Universitas PGRI Adi Buana Surabaya, 2026)
This article examines the neo-modernist thought of Fazlur Rahman regarding the integration of tradition and modernity, as well as its relevance to the reform of Islamic education in Indonesia. The study focuses on three main issues: how Rahman understands the relationship between turats and modernity; how his ideas on the reconstruction of intellectual tradition can be applied to Islamic education; and to what extent this framework can be used to assess the knowledge integration movement in Indonesia. This study employs a qualitative approach through library research, analysing Rahman’s major works and relevant secondary literature. The findings indicate that the integration of tradition and modernity in Rahman’s thought is grounded in the hermeneutics of the ‘double movement’, a historical-critical reading of tradition, and the ethical orientation of the Qur’an. In the field of education, Rahman rejects educational models that merely passively transmit scholarly heritage and emphasises the need for a reconstruction of intellectual tradition capable of linking religious knowledge, modern science, and moral responsibility. This study also demonstrates that the knowledge integration movement in Indonesia has developed at the levels of vision and institutional framework, but often remains limited to symbolic integration, such as the inclusion of verses, hadiths, or Islamic studies courses. The contribution of this article lies in the use of Rahman’s framework as an epistemological critical tool to distinguish symbolic integration of knowledge from integration that genuinely reconstructs the way of thinking in Islamic education.